The Logic of Legal Argumentation: Multi-Modal Perspectives - Xu, Cihua; Zhang, Chuanrui (Informal Logic, 2026)
This article reviews Marko Novak’s (Routledge 2024) The Logic of Legal Argumentation: Multi-Modal Perspectives.